PENGELOMPOKAN MAHASISWA BERDASARKAN MOTIVASI BELAJAR MENGGUNAKAN K-MEANS (STUDI KASUS: PRODI SISTEM INFORMASI STMIK DHARMA WACANA) - Hanifah, Yolanda; Syaputra, Muhammad Adie (Institut Bakti Nusantara, 2024)
Student motivation to learn can be seen from the student's initiative in using their time to study. There are several factors that influence students to be motivated in learning. In this study, researchers used variables in the form of intrinsic motivation, extrinsic motivation, learning goals, learning satisfaction, learning attitudes and perceived value to find out students who had high, medium or low motivation. This research uses K-Means to group students based on learning motivation to find out how much motivation students have in learning.